Co-governance of online car-hailing operation based on passenger feedback - Chen, Jinlong; Chen, Xinrui; Wu, Lijuan; Bilan, Yuriy (Transport, 2025)
The illegal operation of online car drivers is a recurring issue that has garnered significant societal attention. The literature has investigated this problem primarily from the perspectives of the government, platforms, and drivers, while the mechanisms for co-governance among different stakeholders in addressing illegal online car-hailing operations have received limited focus. Additionally, the role of passengers in the online car-hailing process has not been sufficiently explored, leading to a lack of systematic research conclusions and inherent limitations. To analyse the evolutionary equilibrium strategies of participants under various scenarios and their influencing factors, a tripartite evolutionary game model involving passengers, drivers, and online car-hailing platforms was constructed. The decision-making behaviours of these stakeholders were examined through numerical simulation. The results indicate that by strengthening investigations and addressing illegal behaviours, online car-hailing platforms can significantly reduce the likelihood of drivers′ illegal operations. Furthermore, increasing the amount of guarantee deposits can increase drivers′ respect for regulations. Additionally, improving passenger satisfaction can be achieved by increasing compensation for participation in co-governance and increasing promotional rewards from platforms, thereby enhancing service quality. Strengthened supervision strategies not only boost platforms′ social reputation and management efficiency but also create positive incentives for strict supervision through penalty income. This study provides a theoretical foundation for optimizing the supervision of the online car-hailing industry, emphasizing the critical roles of strict supervision, positive incentives, and public participation in elevating service standards. The findings enrich the theoretical understanding of online car-hailing market supervision and offer innovative co-governance strategies aimed at fostering the healthy development of the online car-hailing market.